Assessing media competence: a critical approach from the pedagogical, political and methodological perspectives - Mateus, Julio-César (2019)
This article addresses the importance of developing an instrument that measures media competence, that is, the set of abilities to interact critically with the media. It introduces the problem of media education in the information society and argues the need to assess the skills of citizens in this context. It approaches this need from three perspectives: the pedagogical challenge that implies the little knowledge of the media competence and its little institutional formalization; the political discourse that privileges educational technology over media education; and the methodological question, analyzed from recent assessments of media competence applied in Spain, Chile and Peru, limited to the self-perception. Finally, we propose the construction of an instrument involving two features: integrative in terms of content, and innovative in terms of methodology.